Arah Kiblat dalam Perspektif Fikih dan Geometri - Ismail, Ismail (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2022)
Facing qibla is prayer mandatory, no debate done. The problem arises when people who are away from mecca had to "face" the Qibla during prayers. The difference of fukaha ijtihad was in syat}r meaning. Linguistically syat}r means direction, intent, and purpose. In addition, syat}r also means al-Nishf and al-Wasath. The two meanings used to assume Earth is spherical, then the syat}r Kakbah means can be conceived in geometric paradigm. This research uses descriptive analysis method with integration-interconnection approach, namely examining the qibla direction concept in the Fiqh point of view by utilizing geometry analysis. The results showed that the fukaha perspective could be integrated with geometry concept using the Syat}r Kakbah concept of which is interpreted as "a vertical semicircular plane through the Kakbah". It means, every place on earth's surface will form a Syat}r Kakbah with that place, this plane that becomes the Qibla direction boundary for Muslims in any hemisphere, this has the same value as 'ain al-Kaaba.